Educating Students on the Implementation of the Juvenile Criminal Justice System Law (UU SPPA): Legal Protection and Guidance for Children in Conflict with the Law at SMA Al Islah, Kampung Kebon Cau, Mekar Kondang Village, Sukadiri, Tangerang Regency - Endang Sudarman; Muhamad Qustulani (IRDH International Journal of Social Sciences & Humanities, 2025)
The Juvenile Criminal Justice System Law (UU SPPA) provides legal protection and regulates the development mechanisms for children in conflict with the law. Tangerang Regency, as an area with a large student population, requires efforts to improve legal understanding among the younger generation to foster legal awareness from an early age. This community service activity was conducted in the form of a seminar at a high school in Tangerang Regency, involving 35 students as active seminar participants and 65 other students as interview respondents to obtain a general understanding of the Juvenile Criminal Justice System Law. The seminar material included an introduction to the concept of the Juvenile Criminal Justice System Law, the principles of child protection in the legal process, diversion mechanisms, and the roles of schools, law enforcement, and the community in developing the development of children in conflict with the law. The methods used included presentations, case studies, group discussions, and interactive question-and-answer sessions. The results showed a significant increase in understanding among seminar participants, with an average post-seminar score of 37% higher than before the seminar. Meanwhile, interviews with 65 non-participating students indicated an increase in general awareness of children's rights and obligations, although in-depth understanding remained limited. This activity sparked a commitment from students to disseminate legal knowledge to their peers through student council (OSIS) and extracurricular activities. This article recommends implementing ongoing seminars in other schools in Tangerang Regency, establishing student groups for legal awareness, and integrating children's legal education into school development programs.